DEVELOPMENT OF A 360° VIRTUAL REALITY-BASED ANDROID APPLICATION FOR CAMPUS INTRODUCTION AT WASTUKANCANA COLLEGE OF TECHNOLOGY USING MDLC METHOD - Rohmat Rohmat; Muhammad Rafi Muttaqin; Yusuf Muhyidin (Universitas Nusa Cendana, 2025)
This study aims to develop a 360 Virtual Tour application based on Android as an interactive medium to introduce the campus environment of Sekolah Tinggi Teknologi Wastukancana to new students. The application integrates Virtual Reality (VR) technology to provide an immersive exploration experience through 360 panoramic views. Key features include hotspot-based navigation between scenes, automatic audio narration using text-to-speech, and a stereoscopic display mode compatible with Google Cardboard. The development follows the Multimedia Development Life Cycle (MDLC) method, consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The application was implemented using Unity 2021.3.45 LTS and C# programming language, along with gyroscope sensor support to align the panorama with the user's viewing direction. Functional testing using the blackbox method was conducted with 177 test cases, all of which passed successfully with a 100% success rate. The APK file was distributed through GitHub and Google Sites for direct access by new students. Initial feedback indicated that the application is visually appealing, user-friendly, and capable of delivering a virtual tour experience that closely resembles the real campus environment. These results suggest that the application is effective as a digital campus introduction tool that is informative, practical, and innovative.